Metformin Regulating miR-34a Pathway to Inhibit Egr1 in Rat Mesangial Cells Cultured with High Glucose - Can Wu; Ningning Qin; Huiwen Ren; Min Yang; Shuang Liu; Qiuyue Wang (International Journal of Endocrinology)
Background. Activating AMPKα negatively regulates Egr1 to inhibit inflammatory cytokines in high glucose. miR-34a inhibition increases phosphorylated AMPKα through mediating SIRT1 to suppress the development of fatty liver. Aim of the Study. To clarify the function of Egr1 on the inflammation and fibrosis in high glucose-cultured MCs, as well as to explore the effects of metformin on miR-34a pathway and Egr1 expression. Methods. We transfected MCs with miR-34a inhibitor. And MCs were transfected with small interfering RNA for silencing Egr1 and SIRT1. Quantitative real-time PCR was used to assay the transcription levels of Egr1 mRNA and miR-34a. Western blot was used to test the protein. And ELISA was used to measure inflammatory factors. Results. High glucose upregulates Egr1 to aggravate the inflammation and fibrosis in MCs. miR-34a suppresses the activation of SIRT1/AMPKα and results in promoting Egr1 in high glucose-cultured MCs. Metformin attenuates high glucose-stimulated inflammation and fibrosis in MCs by regulating miR-34a-mediated SIRT1/AMPKα activity and the downstream Egr1 protein. Conclusion. We enriched the effects of miR-34a pathway regulating Egr1 in high glucose-cultured MCs. It provides a foundation for future researches considering Egr1 as a therapeutic target and a new direction for the clinical application of metformin in early DKD.